Local government : an international perspective - Owens, Jeffrey; Panella, Giorgio (Elsevier Science Pub. Co., 1991)
Selection of papers and communications presented at a conference on Local Government Finance held in Pavia, Italy on 29-30 May 1989. The discussions were divided into four main areas: I: The rationale for decentralization; II: The financing of local government: an overview; III: The Financing of local government : grants and equilisation policies and IV: Controlling local government. In each area, both theoretical and policy issues were discussed and an attempt made to identify the lessons that Italy could learn from the experciences of other countries